Diversity of Three Small Type’s Giant Clams and Their Associated Endosymbiotic Symbiodiniaceae at Hainan and Xisha Islands, South China Sea - Chao, Qiqi; Gu, Zhifeng; Wang, Aimin; Liu, Chunsheng; Yang, Yi (Frontiers in Marine Science, 2021)
Giant clams are found in a mutualistic association with Symbiodiniaceae dinoflagellates, however, the diversity of giant clams, as well as the diversity and distribution of Symbiodiniaceae in different Tridacnine species remain relatively poorly studied in the South China Sea. In this study, a total of 100 giant clams belonging to small type’s giant clams, Tridacna maxima, T. crocea and T. noae, were collected from Hainan and Xisha Islands. Based on COI and 16S rRNA fragments, T. maxima and T. crocea showed a closer phylogenetic relationship than T. noae. All three species of giant clams hosted Symbiodiniaceae including genera Symbiodinium (formerly Clade A) and Cladocopium (formerly Clade C). Geographically, symbionts in Cladocopium are restricted to Xisha Islands, probably because Cladocopium prefers to inhabit in waters with higher mean temperatures. The endosymbiont specificity among the three giant clam species was also detected. T. noae and T. crocea are found to harbour Symbiodinium preferentially, compared to Cladocopium. These results could provide important information to understand various endosymbionts occurring in giant clams in the South China Sea.